Citizen Science Project (CSP)-Based Learning Model to Improve Problem-Solving Skills of Biology Education Students - Susiati, Asih Luklu; Azis, Andi Asmawati; Muis, Abd; Bahri, Arsad (Biology Teaching and Learning, 2025)
Abstract. This study aims to explore the problem-solving skills of biology education students and to develop innovative strategies through the implementation of a Citizen Science Project (CSP)–based learning model. The research employed a descriptive quantitative approach involving 28 students from the Biology Education Study Program. The research instruments consisted of a problem-solving test and a needs-analysis questionnaire. The findings indicate that students’ problem-solving skills are still within the medium-to-low category, with an average score of 43.42%. The Real-World Applications indicator achieved the highest score, while the Identify Situation indicator recorded the lowest. These findings highlight a gap between students’ analytical abilities and their conceptual-procedural skills. The implementation of CSP is considered to have strong potential to bridge this gap, as it fosters students’ engagement in solving authentic problems in collaborative, contextual, and applied ways. Accordingly, CSP holds significant promise for enhancing critical, creative, and solution-oriented thinking skills among biology education students.Keywords: 21st century skills, Citizen Science Project, learning innovation, problem-solving skills, student collaboration.